SISTEM INFORMASI PAJAK BUMI DAN BANGUNAN PADA KANTOR CAMAT TANJUNG KEMUNING KABUPATEN KAUR PROVINSI BENGKULU - Liza Yulianti; Aji Sudar sono (UNIVED Press, 2011)
The research aims to create a system of property tax information at the sub-district office Tanjung Kemuning Kaur Regency in Bengkulu Province using Visual Basic 6.0. This program is expected to assist in providing property tax information to employees of the District and the villages in the District of Tanjung Kemuning Kaur Regency in Bengkulu Province. The method used in this study: data collection methods proposed are methods of Library Studies and Observation. From the discussion of the results obtained from this process is the set list assessment report due, recapitulation tax payments and tax returns owed. The program was created by using Microsoft Access and Microsoft Visual Basic 6.0 as a tool. Keywords: Information Systems, Visual Basic 6.0, Land and Building Tax